ЎҚУВЧИЛАРНИНГ ДАРСДАН ТАШҚАРИ ФАОЛИЯТИНИ ТАШКИЛ ЭТИШ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In the current era of man-made civilization, real opportunities have appeared for a significant increase in human free time. Free time is one of the important means of personality formation and has a direct impact on production and labor. Reactive and regenerative processes that help eliminate negative physical and mental stress take place in free time. The use of free time by young people is a unique indicator of culture, and through forms of organization of free time, it becomes easier for young people to understand values and their cultural level. This article is dedicated to the effective organization of students' free time.
Keywords: methodology, psychology, heterogeneous, stress, regenerative process, free time.